La Théologie Trinitaire d’Athanase d’Alexandrie. By Xavier Morales - Teal, Andrew (The journal of theological studies, 2008)
In this important and detailed book, Morales contributes to a nuanced and textually detailed clarification of Athanasius’ trinitarian theology by modest proposals and observations. In Part I of the monograph, in a thematic exploration of terms that distinguish Father, Son, and Spirit, he explores ὑπόστασις (pp. 21–88), terms describing the procession of the persons (pp. 89–154), terms describing the relation between the divine persons differentiated from those whose proper context is the divine economy and God's mission to creation (pp. 155–200), and terms appropriate to describing the relation of Father, Son, and Spirit (pp. 201–31).